2015
DOI: 10.1073/pnas.1507882112
|View full text |Cite
|
Sign up to set email alerts
|

PRUNE2 is a human prostate cancer suppressor regulated by the intronic long noncoding RNA PCA3

Abstract: Prostate cancer antigen 3 (PCA3) is the most specific prostate cancer biomarker but its function remains unknown. Here we identify PRUNE2, a target protein-coding gene variant, which harbors the PCA3 locus, thereby classifying PCA3 as an antisense intronic long noncoding (lnc)RNA. We show that PCA3 controls PRUNE2 levels via a unique regulatory mechanism involving formation of a PRUNE2/PCA3 double-stranded RNA that undergoes adenosine deaminase acting on RNA (ADAR)-dependent adenosine-to-inosine RNA editing. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(212 citation statements)
references
References 32 publications
(34 reference statements)
11
201
0
Order By: Relevance
“…For example, evidence shows that MALAT1 is downregulated in breast cancer, and that knockdown of MALAT1 induces the EMT program, via pathways involving phosphatidylinositide-3 kinase (17). It has also been found that the intronic lncRNA prostate cancer-associated 3 regulates protein prune homolog 2, a human prostate cancer suppressor (25). Furthermore, the lncRNA HOTAIR promotes cell migration and invasion through downregulation of RNA-binding motif protein 38 in hepatocellular carcinoma cells, with increased HOTAIR expression showing promise as a novel biomarker for the diagnosis and/or prognosis of hepatocellular carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence shows that MALAT1 is downregulated in breast cancer, and that knockdown of MALAT1 induces the EMT program, via pathways involving phosphatidylinositide-3 kinase (17). It has also been found that the intronic lncRNA prostate cancer-associated 3 regulates protein prune homolog 2, a human prostate cancer suppressor (25). Furthermore, the lncRNA HOTAIR promotes cell migration and invasion through downregulation of RNA-binding motif protein 38 in hepatocellular carcinoma cells, with increased HOTAIR expression showing promise as a novel biomarker for the diagnosis and/or prognosis of hepatocellular carcinoma (26).…”
Section: Discussionmentioning
confidence: 99%
“…Websites reviewed in (Fritah, et al 2014 (Rehmsmeier, et al 2004) has been used to examine miRNA/lncRNA interaction (Zhou, et al 2017a) http://bibiserv.techfak.unibielefeld.de/rnahybrid/ Increased by androgens in prostate cancer cells (Salameh, et al 2015) Suppressed by ERβ PCa-specific urine biomarker (Laxman, et al 2008 Represses onco-miR-21 (Zhang, et al 2013) inhibited miR-103 in EC cells (Guo, et al 2015) inhibited activation of the AKT/mTOR pathway in PC3 PCa cells (Xue, et al 2016a) Low expression correlated with poor prognosis in thyroid cancer tissues, co-immunoprecipitates with PI3K in HEC-1B EC cells Downregulated in breast , prostate , endometrial Sun et al 2017a), and PTC (Murugan et al 2017) tumors…”
Section: Declaration Of Interest and Fundingmentioning
confidence: 99%
“…Solubilization of membrane proteins in PBS containing 1 mM CaCl 2 , 1 mM MgCl 2 , 50 mM n-Octyl-β-D-glucopyranoside, and PI cocktail (column buffer) was performed as described (58). Immunoprecipitation was performed by using a total of 2 × 10 6 confluent cells for preparation of the membrane extract based on previously reported techniques (59). Cells were solubilized in 1 ml of lysis buffer: 50 mM Tris-HCI (pH 7.4), 150 mM NaCl, 1% NP-40, 0.25% sodium deoxycholate, 1 mM EGTA, 1 mM EDTA, 2.5 mM Na 3 VO 4 , 1 mM NaF, and 1 mM β-glycerophosphate, containing antiprotease cocktail from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%